Incentivos fiscales y otros requisitos básicos para el desarrollo agrícola en Colombia (2020)
This article summarizes the results of research on agricultural development in Colombia within the framework of fiscal policy based on the last two tax reforms, as well as the identification of factors necessary for generating development in this important economic line. The research begins with a review of the documentation on the behavior of the agricultural sector in relation to the contents of the tax statute, making a comparison with the experience of countries such as the United States, Mexico and Ecuador, given the level of trade relations of agricultural products with these countries. It shows that Colombia is at a disadvantage in relation to practices such as agricultural taxation, subsidies, advice, infrastructure, credit facilities and costs.